1997
DOI: 10.1080/014461997372971
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable construction: principles and a framework for attainment

Abstract: The evolution of the concept of sustainable development is used as a basis for advancing understanding of sustainable construction. Principles of sustainable construction are developed and divided into four 'pillars' - social, economic, biophysical and technical - with a set of over-arching, process-oriented principles, to be used as a checklist in practice. A multi-stage framework is proposed which requires the application of Environmental Assessment and Environmental Management Systems for construction proje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
302
0
6

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 440 publications
(310 citation statements)
references
References 10 publications
2
302
0
6
Order By: Relevance
“…In 1990, the world Conservation Strategy observed that sustainable development had been criticized as ambiguous because the term had been used interchangeably with 'sustainable growth' that was a contradiction since nothing can grow indefinitely (Hill and Bowen 1997). From this realization, a reconceptualisation of sustainable development was done.…”
Section: The Concept Of Urban Growthmentioning
confidence: 99%
“…In 1990, the world Conservation Strategy observed that sustainable development had been criticized as ambiguous because the term had been used interchangeably with 'sustainable growth' that was a contradiction since nothing can grow indefinitely (Hill and Bowen 1997). From this realization, a reconceptualisation of sustainable development was done.…”
Section: The Concept Of Urban Growthmentioning
confidence: 99%
“…Biological sustainability includes the motion that sustainable construction needs to protect the natural environment rather than pollute, encourages the use renewable sustainable and reduce the use of water, energy, materials and land in each stage of a project. Technical sustainability requires high performance, durability, quality and mixed use of a building (Hill and Bowen, 1997).…”
Section: Sustainable Constructionmentioning
confidence: 99%
“…The organizations are flexible and are able to integrate new developments in the field of sustainability in their strategy and organizational processes (Hill and Bowen, 1997; Van der Waals and Venneulen, 2000). Highly innovative organizations are participating in (inter)national r&d projects in which radical innovations in the field of sustainability are developed, tested and improved and partners in the network of sustainable innovative organizations are found (Curwell et al, 1999;Glaumann et al, 1999;Kimata, 1999;Larsson and Cole, 2001;Mackley and Milonas, 2001).…”
Section: Interactions Between Public and Private Organizations In Susmentioning
confidence: 99%
“…Standards are being developed that prescribe a minimum sustainable performance leve1 in construction projects (Larsson, 1996;Larsson, 1999;Bon and Hutchinson, 2000) and sustainable construction projects are being developed by multidisciplinary teams consisting of specialists working for different organizations like the authorities, real estate developers, architects, consultants, and contractors (Hill and Bowen, 1997;Ngowi, 1998;Van der Waals and Vermeulen, 2000;Rohracher, 2001). Multidisciplinary teams are activated early in the project and are stimulated to brainstorm about their contributions to the sustainable innovation process (Rohracher, 2001).…”
Section: Interactions Between Public and Private Organizations In Susmentioning
confidence: 99%
See 1 more Smart Citation